Risk Assessment Approach in Airport Security - Sadono, Mahardi; Harahap, Saphira Alifa; Putra, Dani Yulianto; Randhy, Randhy; Nurhakim, Muhamad Luthfi Imam (Universitas Lampung, 2017)
Naturally, the threat to flight is generated from all activities at the airport by passenger or freight. With the growth of air transport, the level of threat to flight activity will also increase. Due to ensure the security of passengers, staff, and all elements of the airport, the airport as a place of the flight operations need a reliable protection system. The purpose of this study is to develop a methodology for assessing the risk level at the airport in order to improve the level of protection at the airport. The level of threats that could jeopardize airport security is categorized into several levels, then analyzed to what extent the risk level can be tolerated as a reference to the formulation of standard protection systems at the airport. The results of this study can be used to deal with threats that occur in the airport through preventive action by setting up a reliable protection system. The risk assessment approach also able to evaluate the airport's existing protection system whether it is tolerable to deal with threats or not, so action can be taken to improve the protection system if the failure rate is still high and have massive consequences to the all airport elements.Keywords— airport security, failure rate, protection system, risk assessment, tolerable risk level.